Genetic Inconsistency in Paternity Investigation - Nurhantari, Y; Suryadi, H (KnE Life Sciences, 2019)
DNA fingerprint is one of forensic identification method and has high accuracy. However, genetic inconsistency such as STR mutation in paternity testing may give complexity to the analysis and resolution of the investigation of the case. This study was aimed to analyze the presence of genetic inconsistency or mutation of DNA marker in paternity test cases which came to Department of Forensic Medicine, Dr. Sardjito Hospital/Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, Indonesia. Totally 58 cases were analyzed from DNA testing cases from 2008 to 2016. Dried bloodstain samples were collected on FTA card after informed-consent and DNA extraction was done directly from FTA card. Amplification was done using commercially available kits and genotyping using ABI Prism 3500 for minimum 15 loci of STR, which are D8S1179, D21S11 CSF1PO, D7S820, D13S317, THO1, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818, and FGA. As results, there was a single mutation of STR repeats at FGA and D12S391 loci. The mutation at D12S391 locus is a loss of a single repeat of paternal allele. However, at FGA locus is unknown either loss or gain neither repeats nor occurred in paternal or maternal allele. In conclusion, a single repeat mutation was observed at FGA and D12S391 loci. Keywords: maternal, mutation, paternal allele, paternity test, STR